2023
DOI: 10.1007/s00402-023-04820-2
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative 3D imaging in plate osteosynthesis of proximal humerus fractures

Abstract: Introduction Proximal humerus fractures are common and often associated with osteoporosis in the elderly. Unfortunately, the complication and revision rate for joint-preserving surgical treatment using locking plate osteosynthesis is still high. Problems include insufficient fracture reduction and implant misplacement. Using conventional intraoperative two dimensional (2D) X-ray imaging control in only two planes, a completely error-free assessment is not possible. Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In a recently published study, we have already demonstrated, contrary to previous opinion, that it is possible to perform intraoperative 3D DVT on the shoulder with an isocentric mobile C-arm in the usual parasagittal position to the patient [ 15 , 38 ]. In a retrospective evaluation of these images, we were able to additionally demonstrate the imageability of the entire AC joint (lateral clavicle, coracoid, and acromion) with regard to the current question.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…In a recently published study, we have already demonstrated, contrary to previous opinion, that it is possible to perform intraoperative 3D DVT on the shoulder with an isocentric mobile C-arm in the usual parasagittal position to the patient [ 15 , 38 ]. In a retrospective evaluation of these images, we were able to additionally demonstrate the imageability of the entire AC joint (lateral clavicle, coracoid, and acromion) with regard to the current question.…”
Section: Discussionmentioning
confidence: 95%
“…In our present DVT navigated SD study, the conditions were adapted to everyday surgical practice and the system setup in the operating room was identical to the in vivo study on intraoperative 3D C-arm visualization of the shoulder joint [ 15 ]. As in the two studies by Stübig et al, the CC drill channels in our study could be placed very precisely in a line always centered on the clavicle and the coracoid [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations